Middle East oil money and its future expenditure - Fallon, Nicholas (London : Graham and Trotman ; [New York] : Crane, Russak, 1975)
A description of the economics of the oil-producing countries requires attention to history, and their possible future developments need to be placed against a worldwide background. The first part of this book examines fundamentals of the oil situation before going on to forecasts of the revenues and wealth of the producing countries, with emphasis on the interdependence of producers and consumers.
Includes bibliographical references and index.
kjo 15/01/2019
Loans
Keywords: Petroleum industry and trade--Finance; Petroleum products--Prices; Petroleum industry and trade; Economic policy; Middle East